Increasing Incidence of Optic Nerve Hypoplasia/ Septo-Optic Dysplasia Spectrum: Geographic Clustering in Northern Canada. (1st June 2016) - Rodd, C; Khaper, T; Bunge, M; Clark, I; Rafay, M; Mhanni, A; Kirouac, N; Sharma, A; Wicklow, B
Abstract: BACKGROUND: Since optic nerves and pituitary gland are embryologi-cally related, optic nerve hypoplasia (ONH) and septo-optic dysplasia (SOD) represent a clinical spectrum associated with visual impairment, pituitary deficiencies, and severe CNS structural malformations(SODplus). ONH is a leading cause of pediatric blindness in North America; genetic mutations are rarely observed. We recently perceived an increase in the number of children with SOD in our clinic. Similarly, several studies have reported a rise in the incidence of ONH/SOD in other jurisdictions. OBJECTIVES: Our primary objectives were to examine trends in annual incidence in Manitoba and geographical clustering in our catchment area ofManitoba, NW Ontario and Nunavut. DESIGN/METHODS: This was a retrospective 1996-2015 chart review from all medical services (Neurology, Ophthalmology, Endocrinology, Genetics) caring for these children to extract information pertaining to anthropometric measures, radiologic findings, parental characteristics, endocrinopathies, and neurologic symptoms. Postal codes were used to assign map co-ordinates and census-based material and social deprivation indices. Numbers of children from Manitoba only were used to calculate annual incidence. From 2010-2014, a Quality Assurance (QA) sub-study identified all pediatric radiology reports containing the words 'optic nerve'; the additional cases of ONH/SOD children not identified by chart review were used to better define the true incidence in Manitoba. RESULTS: Ninety-three children were identified in our catchment area by chart review; Poisson regression confirmed a striking 1.11-fold annual increase (95%CI=1.07-1.16) or 800% over two decades. The annual incidence (averaged 2010-2014) reached 53.3 per 100, 000 affecting 1 in 1875 live births (chartdata). Including children identified by QA sub-study, the incidence rose to 113.3 per 100, 000 live births in Manitoba. These are much higher than previously reported. Most children ( 60%) had SODplus. Common presenting or follow-upfeatures were hypoglyce-mia, nystagmus, seizures, and developmental delay (50%); 40% had hormone deficiencies; 80% (75/93) had reduced visual acuity, typically bilateral. Many childrenwere born prematurelywith young (mean 21y: IQR 19-26y), primiparous mothers. Unhealthy maternal lifestyles and severe material deprivation were noted. There wasdisproportionate clustering in Northern Manitoba (3 times the average provincial rate) and in Nunavut. CONCLUSION: We noted a dramatic rise in the annual incidence of ONH/SOD in Manitoba, NW Ontario and Nunavut, which is much higher than previous reports. This disorderwas strongly associated with poverty in northern communities. The temporal picture was consistent with environmental, nutritional, or toxic etiologies. About half of the children were severely affected with increased morbidity and health care burdens.